Impact of Obesity on the Management and Clinical Course of Patients with Inflammatory Bowel Disease. Issue 12 (December 2015) - Seminerio, Jennifer L.; Koutroubakis, Ioannis E.; Ramos-Rivers, Claudia; Hashash, Jana G.; Dudekula, Anwar; Regueiro, Miguel; Baidoo, Leonard; Barrie, Arthur; Swoger, Jason; Schwartz, Marc; Weyant, Katherine; Dunn, Michael A.; et al.
Abstract : Background: Obesity has been linked with a proinflammatory state and the development of inflammatory diseases. Data on the clinical course and treatment of obese patients with inflammatory bowel disease (IBD) are limited. We used an institutional IBD registry to investigate the impact of obesity on IBD severity and treatment. Methods: This was a retrospective analysis of prospectively collected data for 3 years (2009–2011). Patients with IBD were categorized by body mass index (BMI). IBD-related quality of life, biochemical markers of inflammation, comorbidities, health care utilization, and treatment were characterized. Obesity was defined as a BMI ≥30 (type I: 30–34.9, type II: 35–39.9, and type III ≥40). Results: Among 1494 patients with IBD, 71.9% were above their ideal BMI and 31.5% were obese. Obesity was more common in ulcerative colitis compared with patients with Crohn's disease ( P = 0.04). Obese class II and class III patients were predominantly female. Obesity in IBD was associated with female gender ( P < 0.0001), diabetes mellitus ( P < 0.001), hypertension ( P < 0.001), hyperlipidemia ( P < 0.001), poor quality of life ( P < 0.0001), and increased rates of C-reactive protein elevation ( P = 0.008). In logistic regression analysis, quality of life and C-reactive protein elevation were not independently correlated with obesity. There was no association between increasing BMI and annual prednisone use, emergency department visits, hospitalization, and surgery. Obesity was associated with lower milligrams per kilogram doses of purine analogs and biologics. Conclusions: Obesity in IBD is not associated with increased health care utilization and IBD-related surgeries. Optimal regimens for drug dosing in obese patients with IBD have yet to be defined. Abstract : Article first published online 1 August 2015.